CASP1 variants influence subcellular caspase-1 localization, pyroptosome formation, pro-inflammatory cell death and macrophage deformability - Kapplusch, Franz; Schulze, Felix; Rabe-Matschewsky, Sabrina; Russ, Susanne; Herbig, Maik; Heymann, Michael Christian; Schoepf, Katharina; Stein, Robert; Range, Ursula; Roesen-Wolff, Angela; Winkler, Stefan; Hedrich, Christian Michael; et al. (Clinical Immunology, 2019)
CASP1 variants result in reduced enzymatic activity of procaspase-1 and impaired IL-1β release. Despite this, affected individuals can develop systemic autoinflammatory disease. These seemingly contradictory observations have only partially been explained by increased NF-κB activation through prolonged interaction of variant procaspase-1 with RIP2. To identify further disease underlying pathomechanisms, we established an in vitro model using shRNA-directed knock-down of procaspase-1 followed by viral transduction of human monocytes (THP-1) with plasmids encoding for wild-type procaspase-1, disease-associated CASP1 variants (p.L265S, p.R240Q) or a missense mutation in the active center of procaspase-1 (p.C285A). THP1-derived macrophages carrying CASP1 variants exhibited mutation-specific molecular alterations. We here provide in vitro evidence for abnormal pyroptosome formation (p.C285A, p.240Q, p.L265S), impaired nuclear (pro)caspase-1 localization (p.L265S), reduced pro-inflammatory cell death (p.C285A) and changes in macrophage deformability that may contribute to disease pathophysiology of patients with CASP1 variants. This offers previously unknown molecular pathomechanisms in patients with systemic autoinflammatory disease.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Apoptosis-associated speck-like protein containing a CARD (ASC); Caspase-1; Gasdermin D; IL-1β; Inflammasome; Interleukin-1 converting enzyme; NLRP3; Pyroptosis; Pyroptosome; Speck